2D Multilayer solution for an electrified road with a built-in charging box. (31st July 2019) - Chabot, Armelle; Deep, Pawan
Abstract : Charging electric vehicles inductively as they are being driven on the road is a conceivable option through a prefabricated charging box placed underneath the top asphalt layer of existing flexible pavements. Such a box inclusion however generates a material discontinuity in the pavement layer and points of singularities, inducing failure in the materials involved under heavy moving loads. To design such an electrified road, the specific model proposed here yields parametric calculations of multilayered structures embedded in a crack. By separating the problem into multiple zones across different material layers in a cross-sectional geometry, the multilayered solution presented provides all the mechanical fields and interface stresses between layers. On an electrified road case study from the literature, a vertical crack between box and material layer extends applicability of this mechanical solution to predicting failures like layer debonding. An alternative top pavement layer material is suggested for future developments.